Self-assembled carriers as drug delivery systems: current characterization challenges and future prospects - Pantelić, Ivana; Ilić, Tanja; Nikolić, Ines; Savić, Snežana (Archives of Pharmacy, 2023)
A review of recent publications reveals an increased interest in the so-called self-assembled carriers and their applicability in drug delivery via various routes of administration. Self-assembly denotes the process of rather spontaneous formation of ordered aggregates (sometimes under specific conditions – e.g., pH, temperature, ionic strength), via diverse interactions. This process, seen in many naturally occurring substances (polysaccharides, proteins, lipids), has inspired researchers to synthetize innovative self-assembling materials or combinations of existing ones. This paper provides a review of the recently investigated self-assembling materials and the carriers they form, often belonging to the sphere of pharmaceutical nanotechnology. Self-assembled carriers may provide enhanced stability, more efficient encapsulation and/or controlled delivery of active pharmaceutical ingredients. However, the diversity of geometries obtained (spheres, polyhedrals, ellipses, discs, porous structures, etc.) presents a significant characterization challenge, often requiring the application of several complementary techniques for proper evaluation of carrier size and morphology. Commonly utilized characterization techniques for investigating physico-chemical and certain biopharmaceutical properties are discussed, along with their advantages and disadvantages. Finally, the authors offer their critical opinion on the outlook of self-assembled drug carriers.